Islamic wealth management towards retirement planning among private sector workforce in Malaysia - Mohd Sadad, Mahmud; Nik Hazimi, Mohammed Foziah (2018)
Rapid ageing population around the world makes people to live longer, but necessarily not guarantee people with happier or healthier. As developing country, Malaysia has no exception to experience the phenomena of ageing population. Malaysian people still lack of awareness towards retirement savings preparedness. As the mainstream retirement scheme in Malaysia, Employees Provident Fund (EPF) in Malaysia has reported that most of the retirees in Malaysia have inadequate retirement savings to sustain their life when retire. In this regards, Islamic wealth management would have a great role in ensuring the sustainability and well-being of financial planning among the Muslims, especially for retirement savings purposes. Therefore, the study aims to investigate and explore the concept of Islamic annuity to be executed by the authorities such as EPF institution and other financial institutions.